Land and resource administration: farmers, managers, and soldiers in the Great Oasis - Ast, Rodney (The Great Oasis of Egypt, 2019)
This chapter surveys a range of extant textual records (wooden tablets, jar labels, and ostraca) from the Great Oasis related to the management of water wells and of crop distribution. It looks first at the longstanding practice of documenting the condition of the wells in the oasis, before focusing on late antique evidence from both the Dakhla and Kargha oases concerned with the disbursement of these goods and on the individuals responsible for generating the records, primarily literate administrators and members of the military.